2014
DOI: 10.1097/md.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Critical Acute Pancreatitis

Abstract: Critical acute pancreatitis (CAP) has recently emerged as the most ominous severity category of acute pancreatitis (AP). As such there have been no studies specifically designed to evaluate predictors of CAP. In this study, we aimed to evaluate the accuracy of 4 parameters (Acute Physiology and Chronic Health Evaluation [APACHE] II score, C-reactive protein [CRP], D-dimer, and intra-abdominal pressure [IAP]) for predicting CAP early after hospital admission. During the study period, data on patients with AP we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…APACHE II, CRP and IAP levels are good predictors of disease severity in critical acute pancreatitis (22). Previous results indicated that APACHE II and SOFA scores were positively associated with the severity of IAP (20).…”
Section: Discussionmentioning
confidence: 89%
“…APACHE II, CRP and IAP levels are good predictors of disease severity in critical acute pancreatitis (22). Previous results indicated that APACHE II and SOFA scores were positively associated with the severity of IAP (20).…”
Section: Discussionmentioning
confidence: 89%
“…ст.) [6,9,16]. Другие современные маркеры тяжести и прогноза ТОП включают амилоид А, трип-син-активированный пептид [14,17], сывороточный ферритин [3] и цитокины -IL-6, IL-12 и ангиопоэтин-2 плазмы.…”
Section: обоснованиеunclassified
“…This was superior to both Ranson and Glasgow scores at 48 h. Although the APACHE II scoring system has gained some recognition for its performance and fl exibility, the complexity of the system hinders its everyday use [18]. higher mortality by each 1mmHg of PIA>12mmHg [9][10][11][12].…”
Section: Severity Assessmentmentioning
confidence: 99%
“…If it is not accomplished, acinar cells would develop ischemia and necrosis secondary to hipoperfusion [7]. Persistent cytokines release by necrotic tissue would increase vascular permeability favoring pulmonary effusion and respiratory distress, hypovolemia, hypotension, acute renal failure, intestinal edema and intra-abdominal hypertension [8,9].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation